A brain-shuttled antibody targeting alpha synuclein aggregates for the treatment of synucleinopathies - Sungwon An; John J. McInnis; Dongin Kim; Yihang Li; Ozge Tasdemir-Yilmaz; Jinhyung Ahn; Brian C. Mackness; Seung-Hwan Kwon; Julia Maeve Bonner; Miran Yoo; Simon Dujardin; Donghwan Kim; et al. (npj Parkinson's Disease)
Abstract Parkinson’s disease and multiple system atrophy are members of a class of devastating neurodegenerative diseases called synucleinopathies, which are characterized by the presence of alpha-synuclein (α-Syn) rich aggregates in the brains of patients. Passive immunotherapy targeting these aggregates is an attractive disease-modifying strategy, which must not only demonstrate target selectivity towards α-Syn aggregates, but also achieve appropriate brain exposure to have the desired therapeutic effect. Here we present preclinical data for SAR446159, a next-generation antibody for the treatment of synucleinopathies. SAR446159 is a bispecific antibody composed of an α-Syn-binding immunoglobulin and an engineered insulin-like growth factor receptor 1 binding single-chain variable fragment, acting as a shuttle to transport an antibody across the blood-brain barrier. SAR446159 binds tightly and preferentially to α-Syn aggregates and prevents their seeding capacity in vitro and in vivo. The binding properties of SAR446159 combined with its brain-shuttle technology make it a potent immunotherapeutic for treating synucleinopathies.